1989
DOI: 10.1111/j.1365-3040.1989.tb01967.x
|View full text |Cite
|
Sign up to set email alerts
|

A model of nitrogen flows in grassland

Abstract: The model comprises three submodels, which together give an integrated picture of nitrogen pools and fluxes in grassland under grazing or cutting. The first submodel represents the interaction of the grazing animal with the sward through intake and the production of excreta; the second is concerned with the growth of the vegetative grass crop and its response to light, temperature and nitrogen; these two submodels are interfaced with a submodel of soil earbon and nitrogen pools and processes, including dead sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…1). Our experience here and elsewhere (Johnson and Thornley, 1985;Thornley and Verberne, 1989) is that the inc1usion of tissue age categories makes a substantial and important difference to dynamic behaviour (see pp. 176-180 ofThornley and Johnson, 1990, for a general discussion of this point).…”
Section: The Modelmentioning
confidence: 99%
“…1). Our experience here and elsewhere (Johnson and Thornley, 1985;Thornley and Verberne, 1989) is that the inc1usion of tissue age categories makes a substantial and important difference to dynamic behaviour (see pp. 176-180 ofThornley and Johnson, 1990, for a general discussion of this point).…”
Section: The Modelmentioning
confidence: 99%
“…Soil carbon and nitrogen dynamics Friend et al (1997) investigated several approaches to predicting soil carbon and nitrogen dynamics in Hybrid v3.0, including those described by Thornley and Verberne (1989) and Raich et al (1991). They concluded that the CENTURY model (Parton et al, 1987(Parton et al, , 1993 was the best for simulating soil C and N dynamics.…”
Section: Tree Height Diameter 6olume and Mortalitymentioning
confidence: 99%
“…They concluded that the CENTURY model (Parton et al, 1987(Parton et al, , 1993 was the best for simulating soil C and N dynamics. CENTURY can be used for a wide range of litter input rates and soil and climate conditions without requiring detailed parameterization of microbial kinetics as in Thornley and Verberne's (1989) model or different parameterization for different vegetation types as required by Raich et al's (1991) model. The soil C-N sub-model of CEN-TURY has been fully or partly incorporated into other ecosystem models (e.g.…”
Section: Tree Height Diameter 6olume and Mortalitymentioning
confidence: 99%
“…Pasture growth, feed intake, cow liveweight, milk yield (autumn and spring), explore different management and risk scenarios, effect of dairy cow reproduction on farm economic performance. (Moore et al 2007) (Eckard et al 2006;Bryant et al 2007;Cullen et al 2007Cullen et al ,2008Chapman et al 2008;White et al 2008) (Berntsen et al 2005;Hutchings et al 2007) (Ándales et al 2005) (Hill et al 1999;Boschma & Scott 2000;Clark et al 2000Clark et al ,2003Cohen et al 2003;Salmon et al 2004;Bryant et al 2005;Robertson 2006) (Thornley & Verberne 1989;Thornley et al 1995;Cannell & Thornley 1998;Thornley & Cannell 2000;Thornley 2001;Barrettetal. 2004) (Rotz et al 1999b(Rotz et al ,c, 2003Sanderson et al 2001;Corson et al 2006Corson et al ,2007 (Cacho et al , 1999) Wastney et al 2002;Beukes et al 2005aBeukes et al ,b, 2007 was identified, the name of the model and the keyword "simulation" were entered as keywords in web of Knowledge®.…”
Section: Model Identificationmentioning
confidence: 99%
“…The Hurley Pasture Model was developed in Britain in the 1980s (Johnson & Thornley 1985;Thornley & Verberne 1989;Thornley 1998). a full description of the model and associated code is provided in Thornley (1998), with a synopsis provided in Thornley & Cannell (1997).…”
Section: Hurley Pasture Modelmentioning
confidence: 99%